'Soother of mind' – meditation in psychiatric disorders: a narrative review. (March 2022) - Kumar, Vinod; Bhide, Shree Raksha; Arasappa, Rashmi; Varambally, Shivarama; Gangadhar, Bangalore N.
SUMMARY: Meditation, a component of ashtanga yoga, is an act of inward contemplation in which the mind fluctuates between a state of attention to a stimulus and complete absorption in it. Some forms of meditation have been found to be useful for people with psychiatric conditions such as anxiety, depression and substance use disorder. Evidence for usefulness of meditation for people with psychotic disorders is mixed, with reported improvements in negative symptoms but the emergence/precipitation of psychotic symptoms. This article narrates the benefits of meditation in psychiatric disorders, understanding meditation from the yoga perspective, biological aspects of meditation and practical tips for the practice of meditation. We also explain possible ways of modifying meditative practices to make them safe and useful for the patient population and useful overall as a society-level intervention.